Ouabaine Like Effects of Ethanolic Extract of Aerial Parts of Urtica dioica L. on Isolated Rabbit Atrioventricular Node: Potential Role as an Anti - Arrhythmic Plant - V Khori; M Naebpour; A Mir - Abbasi (Institue of Medicinal Plants, ACECR, 2008)
Bachground: The ideal drug for treatment of wide range of supraventricular arrhythmia has yet to be developed. For cardiovascular disease, herbal treatments are suitable alternatives for synthetic drugs due to their availability, minimal side effects and lower price. Previous studies showed antihypertensive, negative inotropic activities of Urtica dioica (Nettle). Objectives: The aims of the present study were: 1) to determine concentration-dependent effects of ethanolic extract of nettle on the nodal basic and functional properties. 2) to campare mechanism of action nettel with ouabaine. Method: Male Newsland rabbits (1-1.3 kg) were used in all of experiments various experimental stimulating protocols (WBCL Recovery, Facilitation, Fatigue) were applied to assessing electrophysiological properties of Node. We used isolated perfused AV-nodal preparation (n=24). All protocols were repeated in the presence and absence (control) of different concentration (0.25 - 0.5-1 g/l) of Nettle and ouabaine(0.1μM). Results were shown as Mean ± SE and a probability of 5% was taken to indicate statistical significance. Results: We had considerable depression in basic and functional properties of node after adding Nettle, as WBCL, Effective refractory period, Functional refractory period and nodal conduction Time significantly increased(p<0.05). In addition magnitude of fatigue (∆AH) and ∆FRP (Amount of facilitation) significantly increased (p<0.05). Conclusion: The above results showed potential antiarrhythmic properties of "Urtica dioica" by increasing fatigue and nodal refractoriness. Therefore, it may be considered for treatment of supraventicular arrhythmias.